THE APPLICATION OF LOUD READING IN TEACHING PRONUNCIATION AT MTsN BANDA ACEH II IN TEACHING - Afna, Mauloeddin (UPT. Pengembangan Bahasa IAIN Zawiyah Cot Kala Langsa, 2016)
This study was conducted to investigate class activity in drilling pronunciation for English subject at junior high school level. It was conducted at MTsN Banda Aceh II, Aceh. To collect the data, the researcher used test, observation and interview. The students were taught by loud to improve students’ pronunciation in English. Several paragraphs were taken in charge of supporting loud reading drills.The drills took 45 minutes in one section. Test was used to identify the success of loud reading in teaching pronunciation. Observation, on the other hand, was designed to observe the school environment, teaching method, and students’ assessment. In addition, interview was carried out informally to the headmaster and teachers of MTsN Banda Aceh II. This study reveals that the mean is 80.2. This shows a positive use of the loud reading applied at the school. The study also exposes that this method is effective to help their reading ability and to maintain their pronunciation. Thus, the researcher concludes that loud reading has been effectively boosted the students’ pronunciation.